2010
DOI: 10.7763/ijcea.2010.v1.57
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Effect of Pollution

Abstract: Global pollution is a major problem that is yet to be solved. There are several causes of increasing pollution such as burning fossils, deforestation, increase in number of industries and vehicles etc. Humans are almost responsible for all types of pollution. The impact on global environment is becoming more serious. These impacts are discussed in this paper along with probable controlling methods of pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Air pollution is a global problem and has negative effects on human, animal and plant health (Kanawade et al, 2010). Pollutants emitted into the atmosphere are deposited at the Earth's surface where they accumulate in soil, sediment, and biota of terrestrial and aquatic ecosystems (Schröder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution is a global problem and has negative effects on human, animal and plant health (Kanawade et al, 2010). Pollutants emitted into the atmosphere are deposited at the Earth's surface where they accumulate in soil, sediment, and biota of terrestrial and aquatic ecosystems (Schröder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Transportation and industry produce emissions such as carbon dioxide and nitrogen oxides that contribute to air pollution in urban areas. Pollution causes ecological effects such as the greenhouse effect, harm to plant and animal health and temperature stress (Kanawade et al 2010). It is damaging to urban biodiversity because several species have become more sensitive to environmental stress from pollution and habitat fragmentation (Uttara et al 2012;Szlavecs et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals are amongst the most hazardous pollutants to living organisms due to their high toxicity and persistence in the environment [1][2][3][4] . Multiple studies showed that heavy metals damage the cell membrane system and negatively affect plant development, growth, and reproduction [5][6][7][8] , generate reactive oxygen species (ROS) 9,10 , and may alter the structure of essential plant biomolecules [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%